1960
DOI: 10.1002/macp.1960.020380102
|View full text |Cite
|
Sign up to set email alerts
|

Di‐isotaktische polymere

Abstract: ZUSAMMENFASSUNG:In Zusammenhang mit isotaktischen Polymeren werden die Struktur und die sterischen RegelmaRigkeiten einer neuen Serie von linearen Polymeren mit Kopf-Schwanz-Verkniipfung beschrieben und definiert. Diese Polymeren sind aus Monomeren mit Athylen-Doppelbindung, in denen beide Kohlenstoffatome der Doppelbindung substituiert sind, erhalten worden. Diese Polymeren mit sterisch regelmaRiger Struktur werden als di-isotaktische Polymere bezeichnet ; sie sind im allgemeinen kristallin und schmelzen bei … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

1963
1963
1999
1999

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 4 publications
4
15
0
Order By: Relevance
“…As in previous papers, 7,8,13,21 the basic models of the alkene-bound intermediates considered in this paper are metal complexes containing three ligands, which are a π-coordinated propene molecule, a σ-coordinated isobutyl (simulating a primary growing chain), and a stereorigid π-coordinated ligand (1)(2)(3)(4).…”
Section: Modelsmentioning
confidence: 98%
See 1 more Smart Citation
“…As in previous papers, 7,8,13,21 the basic models of the alkene-bound intermediates considered in this paper are metal complexes containing three ligands, which are a π-coordinated propene molecule, a σ-coordinated isobutyl (simulating a primary growing chain), and a stereorigid π-coordinated ligand (1)(2)(3)(4).…”
Section: Modelsmentioning
confidence: 98%
“…The mechanism for the Ziegler−Natta polymerization of the olefins, proposed by Cossee , several years ago, consists of two consecutive steps: coordination of the olefin to the catalytic center and insertion into the metal−carbon bond through a cis -opening. This mechanism assumes that, in the insertion step, there is a migration of the growing chain to the position previously occupied by the coordinated monomer (chain migratory insertion). In the following, we will distinguish as “alkene-free” and “alkene-bound” the two possible states of the metal atom, constituting the catalytic center which may have, thus, different degrees of coordinative saturation.…”
Section: Introductionmentioning
confidence: 99%
“…This crude product was purified by column chromatography on silica gel with hexane/ethyl acetate (9:1) as an eluent to give 3.3 g (90%) of 4a as a colorless crystals: mp 76. 5…”
Section: Preparation Of Furfuryl Benzyl Ether (3)mentioning
confidence: 99%
“…In particular, the synthesis of optically active polymers with chirality in the main chain is currently attracting much attention , After Natta et al reported the asymmetric anionic polymerization of methyl sorbate as the first example of asymmetric synthesis polymerization, a number of experiments on the induction of configurational main-chain chirality during polymerization have been demonstrated . The following are the recent successful approaches to the chiral synthetic polymers by asymmetric synthesis polymerization; asymmetric alternating copolymerization of α-olefins with carbon monoxide, asymmetric polyaddition of 1,3-dimercaptobenzene to dibenzylidene acetone, asymmetric cyclopolymerization of dienes with a chiral catalyst, and asymmetric anionic polymerization of achiral N-substituted maleimide. …”
Section: Introductionmentioning
confidence: 99%
“…1) The first is the use of normal stereospecific catalysts wherein at least one group bound to the organometallic compound used in the catalyst preparation, which will be the terminal group of the macromolecules, is optically active (101). In this case the asymmetric induction is probably due to the particular configuration of the terminal group of the growing chain bound to the catalyst.…”
Section: Stereospecificity In Polymerization Of Nonhydrocarbon Monomersmentioning
confidence: 99%